(3eQhL GdPgH heYGOf GdLhgQs - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s
(3ChdgG (B:s
(3PcQ OjGfGJ GdYQH hBQGFgG ai GdLGgdjI hJaQbgG ai GdHdGO NHQ GUMGH Gdajd hYHO GdeWdH hZjQ Pdc s
(3BNQgG (B:s
(3jfJgi HPcQ GdHjhJ GdeYXeI hGdgjGcd GdeTQaI hHjhJ GdfjQGf hjdjg LRA PcQ GdHjhJ GdeYXeI YfO GdjhfGfjjf s
(3fSNI KGfjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(907 / 2 (3b(B) s
Keywords: (3GdJGQjNs